Hygroscopic salts support the stomatal penetration of glyphosate and influence its biological efficacy. Issue 3 (9th May 2014) - Basi, Sabin; Burkhardt, Juergen; Noga, Georg; Hunsche, Mauricio
<x xml:space="preserve">Abstract</x> The objective of this study was to better understand the role of chaotropic and kosmotropic salts in stomatal uptake, a process that occurs in parallel with cuticular penetration and affects the bioefficacy of glyphosate. In Trial 1, salt solutions of kosmotropic (NH4)2SO4 and chaotropic NaClO3, with or without the organosilicone surfactant, Break‐Thru® S233 (BT), and with or without glyphosate, were prepared. In Trial 2, sodium salts with a kosmotropic‐to‐chaotropic nature (Na2SO4, NaCl, NaNO3 or NaClO3) and BT were prepared with or without glyphosate. At very high concentrations, the salts of a kosmotropic nature induced a slight decrease in the surface tension, whereas those of a chaotropic nature triggered a significant decrease in the surface tension. Solution droplets were deposited onto the leaves of Viola arvensis and Chenopodium album. The dried deposits were analyzed with an environmental scanning electron microscope. The salts formed structures linking the exterior to the interior of the stomata in the crystalline ([NH4]2SO4) or amorphous (NaClO3) form. However, the low surface tension alone did not appear to be the unique driving force for stomatal uptake. With glyphosate, amorphous globular structures of glyphosate salt were formed in the Na2SO4 (kosmotropic) solution. Differently, the salts of a rather chaotropic nature (NaNO3 or NaClO3) formed a colloidal matrix. In general, salt residues were observed over the periclinal cell walls and inside the stomatal chamber. Neither (NH4)2SO4 nor Na2SO4 had a significant impact on glyphosate bioefficacy. However, the chaotropic salt, NaNO3, enhanced the bioefficacy of glyphosate the most, with a performance that was comparable to that of the solution glyphosate + organosilicone surfactant.